INVITATION PROJECTS FOR ARCHITECTURAL ROUTES ARCHITECTURAL ENVIRONMENT - Matniyazov Zafarbek Erkinovich (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This article focuses on the development of landscape design projects that have an aesthetic appearance that attracts the roadside side areas of the Aral Sea tourist routes. As a result of the study of tourist routes along the Aral Sea in the Republic of Karakalpakstan; visually unattractive views of tourist roadsides were identified and photographed, public service centers using innovative landscape and design solutions to address the identified problems, as well as recreation areas, ornamental plant species used in extreme landscaping, small architectural devices and landscaping solutions projects have been developed.